Development of Acute Malnutrition Despite Nutritional Supplementation in Malawi. Issue 5 (May 2019) - Kaimila, Yankho; Pitman, Ryan T.; Divala, Oscar; Hendrixson, D. Taylor; Stephenson, Kevin B.; Agapova, Sophia; Trehan, Indi; Maleta, Ken; Manary, Mark J.
Abstract : ABSTRACT: Malnutrition in children is most often attributed to inadequate nutrient intake. Utilizing data from 2 prospective, randomized controlled trials of complimentary feeding with supplemental legumes (n = 693, ages 6–24 months) in 2 Malawian villages, Masenjere, and Limera, we document a high rate 70/693 (10.1%) of acute malnutrition (AM). Risks for AM in this setting, as determined by Cox regression analysis, include study village (hazard ratio [HR] 3.0), prior malnutrition (HR 4.12), stunting (HR 2.87), and a marker of food insecurity (HR 1.89). Comparison of Masenjere to Limera demonstrate adequate and similar nutritional intake yet an increased rate of AM in Masenjere, 56 of 400 (14.0%) versus 14 of 293 (4.8%), and stunting, 140 of 400 (35%) versus 80 of 293 (27%), environmental enteric dysfunction 246 of 400 (71%) versus 181/293 (67%), and infectious symptoms (cough and diarrhea). Masenjere did have cleaner water and less food insecurity 200 of 399 (50.5%) versus 204 of 293 (69.6%). These findings suggest adequate complementary nutrient intake does not protect young children against AM.